A Process for Developing a Common Vocabulary in the Information Security Area - Knop, Jan von (IOS Press, 2013)
This paper aims to give precise definitions characterizing the various concepts that come into play when addressing the dependability and security of computing and communication systems. Clarifying these concepts is surprisingly difficult when we discuss systems in which there are uncertainties about system boundaries. Furthermore, the very complexity of systems (and their specification) is often a major problem, the determination of possible causes or consequences of failure can be a very subtle process, and there are (fallible) provisions for preventing faults from causing failures